Factors influencing user adoption on online sports training services: a systematic review - Wan Abas, Wan Anita; Qi, Wang; Abdullah, Zulhamri (The Elite Scientific Forum Pakistan, 2024)
This research endeavors to perform an in-depth review of literature concerning the propensity of individuals to utilize online sports learning and training services. The investigation delves into both quantitative and mixed-methodological studies that explore user behavior in relation to online sports training apps. By using the PRISMA guidelines, an analysis of 28 scholarly articles, retrieved from the databases of Science Direct and Scopus up until August 2023, was conducted. By proposing a detailed framework, this research illuminates several aspects that influence the adoption of sports training technologies via applications or online services from multiple angles. The findings validate that theoretical frameworks such as the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT) remain dominant in these studies. However, more diverse theories and models are being considered within the context of online sports training. Moreover, this study constructs a cause-and-effect model illustrating key influencers, along with potential moderators and mediators within this framework. These findings can help online sports training developers increase user engagement, enhance physical performance, improve user retention for virtual training programs, and refine the features and services offered by online sports education platforms.